What changes in the biology of bone movement induced with mini-implants/miniplates is the synchronicity - Alberto CONSOLARO; Ertty SILVA; Maurício de Almeida CARDOSO (Dental Press Editora, 2022)
ABSTRACT Introduction: Induced tooth-bone movement occurs by a synchronicity of dental and bone phenomena, thanks to the osteocytic network, which is a three-dimensional network that controls the bone shape or design. Objective: To describe the tooth-bone movement induced by enhanced anchorage, divided into three distinct moments: zero, start and stop. Question: From this description, the main question arises: with the use of mini-implants/miniplates, what changes in the biology of induced tooth-bone movement? The answer is: nothing changes, either biologically or microscopically. Conclusion: This technique optimizes the treatment time, and the range of therapeutic possibilities is broadened, thanks to the synchronicity of phenomena - which remain the same, in all teeth and bones, yet in a synchronized manner. Bone anchorage represents synchronicity in induced tooth-bone movement.